Penerapan Pendidikan Karakter Pada Peserta Didik SMA Manbaul Ulum Boarding School Pondok Aren Tangerang Selatan - Kusnandar; Muhammad Tajuddin (Islah Tarbawi: Journal of Islamic Education and Learning, 2025)
The purpose of this study was to determine the application of character education through the boarding school system as well as the supporting and inhibiting factors in implementing character education for class X students at the boarding school of Manbaul Ulum Boarding School Pondok Aren, South Tangerang. The study was conducted using a qualitative approach and data collection techniques of observation (observation), interviews and documentation so that it can describe the results of research in accordance with the development of student behavior. Based on the results of this study, it can be concluded that character education is applied at SMA Manbaul Ulum Boarding School Pondok Aren, South Tangerang. First, the application of character education through congregational fardhu prayers, tahajjud prayers, prayer beads and dhikr to build the religious character of students, secondly through muhadhoroh activities that can train students in language and build self-confidence, thirdly deepening religious knowledge through book studies. However, it is undeniable that the tight schedule of boarding school activities is a complaint for students, the role of parents is less cooperative, and the discipline that students cannot apply.